EFFICIENCY OF FLUTED PUMPKIN PLANT (TELFAIRIA OCCIDENTALIS) IN THE PHYTOREMEDIATION OF WASTEWATER EFFLUENT FROM SHARADA INDUSTRIAL AREA, KANO STATE, NIGERIA (FUDMA JOURNAL OF SCIENCES, 2020)
Heavy metals tend to accumulate in the environment thereby contaminating the food chain, and as such pose risks to health. In this study the use of fluted pumpkin plant in phytoremediation of heavy metals from soil polluted with heavy metals from Sharada Industrial Area of Kano state Nigeria has been examined. The seeds of the plant were planted in four different planting pots, with one set of pots watered with the effluent collected from the Sharada Industrial Area, and the other set (the control) watered with clean unpolluted water. Prior to planting, the physicochemical parameters of the soil to be used were analyzed, with the pH, the electrical conductivity and the concentrations of the heavy metals all determined. After germination both the samples and controls were subjected to ashing (for the plants) and digestion (for the waste water) and were later subjected to AAS. The results show high concentration ( in mg/L) of heavy metals in the plant sample watered with effluent, that is Cd (2.30); Pb (6.20); Cr (0.70); Zn (3.70); Cu (2.90) and Fe (7.13), while the concentrations ( in mg/L) of these heavy metals were also found to be very high in the Sharada industrial effluent (the waste water sample), that is Cd (2.210); Pb (3.300); Cr (0.500); Zn (5.080);  Cu (3.900) and Fe (2.520). In all the cases the concentrations in the controls were found to be below or within their permissible limits.
Keywords: Effluents, heavy metal, phytoremediation, Telfairia occidentalis.